Psychotropic drugs and the risk of fall injuries, hospitalisations and mortality among older adults. (25th April 2016) - Johnell, Kristina; Jonasdottir Bergman, Gudrun; Fastbom, Johan; Danielsson, Bengt; Borg, Natalia; Salmi, Peter
Abstract : Objective: To investigate whether psychotropics are associated with an increased risk of fall injuries, hospitalizations, and mortality in a large general population of older adults. Methods: We performed a nationwide matched (age, sex, and case event day) case–control study between 1 January and 31 December 2011 based on several Swedish registers (n = 1, 288, 875 persons aged ≥65 years). We used multivariate conditional logistic regression adjusted for education, number of inpatient days, Charlson co‐morbidity index, dementia and number of other drugs. Results: Antidepressants were the psychotropic most strongly related to fall injuries (ORadjusted : 1.42; 95% CI: 1.38–1.45) and antipsychotics to hospitalizations (ORadjusted : 1.22; 95% CI: 1.19–1.24) and death (ORadjusted : 2.10; 95% CI: 2.02–2.17). Number of psychotropics was associated with increased the risk of fall injuries, (4 psychotropics vs 0: ORadjusted : 1.53; 95% CI: 1.39–1.68), hospitalization (4 psychotropics vs 0: ORadjusted : 1.27; 95% CI: 1.22–1.33) and death (4 psychotropics vs 0: ORadjusted : 2.50; 95% CI: 2.33–2.69) in a dose–response manner. Among persons with dementia (n = 58, 984), a dose–response relationship was found between number of psychotropics and mortality risk (4 psychotropics vs 0: ORadjusted : 1.99; 95% CI: 1.76–2.25). Conclusions: Our findings support a cautious prescribing of multiple psychotropic drugs to older patients. © 2016 The Authors. International Journal of Geriatric Psychiatry Published by John Wiley & Sons, Ltd.